Functional Mechanisms and Roles of Adaptor Proteins in Abl-Regulated Cytoskeletal Actin Dynamics. (17th May 2012) - Sato, Mizuho; Maruoka, Masahiro; Takeya, Tatsuo
Abstract : Abl is a nonreceptor tyrosine kinase and plays an essential role in the modeling and remodeling of F-actin by transducing extracellular signals. Abl and its paralog, Arg, are unique among the tyrosine kinase family in that they contain an unusual extended C-terminal half consisting of multiple functional domains. This structural characteristic may underlie the role of Abl as a mediator of upstream signals to downstream signaling machineries involved in actin dynamics. Indeed, a group of SH3-containing accessory proteins, or adaptor proteins, have been identified that bind to a proline-rich domain of the C-terminal portion of Abl and modulate its kinase activity, substrate recognition, and intracellular localization. Moreover, the existence of signaling cascade and biological outcomes unique to each adaptor protein has been demonstrated. In this paper, we summarize functional roles and mechanisms of adaptor proteins in Abl-regulated actin dynamics, mainly focusing on a family of adaptor proteins, Abi. The mechanism of Abl's activation and downstream signaling mediated by Abi is described in comparison with those by another adaptor protein, Crk.